APLIKASI BAHAN ABRASIF TERHADAP KEKASARAN PERMUKAAN RESIN KOMPOSIT: APPLICATION OF ABRASIVE MATERIALS ON SURFACE ROUGHNESS OF COMPOSITES RESIN - Diana Setya Ningsih; Decky Jusiana Indrani (Dentika: Dental Journal, 2010)
Composites resin restoration should be smooth and glossy to improve aesthetic and prevent food retention. Therefore, polishing procedure is needed to reduce surface roughness in order to achieve smooth surface using abrasive materials. The purpose of this article was to discuss the influence of abrasive materials on surface roughness of resin composites. The ability of abrasive materials to reduce surface roughness depends on the three main factors. Grit size and particle orientation give a significant effect on the degree of abrasion of resin composites surface. Mean while, the sharp edge particle has a greater contact point which has an ability to cut more resin composite on the surface rather than round shape particle. Surface roughness of abrasive materials also plays a role for reducing the surface roughness of filler resin composites, therefore alumina oxide is more suitable to make smooth surface of resin composites. In addition, duration application and pressure of abrasive bahan can influence the abrasion rate of surface roughness of resin composites. Therefore, it can be concluded that particle shape and size of abrasive materials, hardness of abrasive materials and duration of application and pressure when application abrasive materials play important role in reducing surface roughness and abrasion rate of resin composites. All of those factors must be concerned in polishing, therefore, the smooth and glossy surface can be obtained.